Uncertainty, Hiring, and Subsequent Performance: The NFL Draft - Hendricks, Wallace; DeBrock, Lawrence; Koenker, Roger (Journal of Labor Economics, 2003)
In this article, we analyze the impact of uncertainty on the hiring process. We show the connection between models of statistical discrimination where uncertainty can work against groups that have less reliable indicators of future productivity and models of option value where uncertainty about future productivity can be beneficial for these groups. These models generate hypotheses about the relationship between ex ante hiring patterns and ex post productivity. This is applied to the market for NFL football players. We provide various estimates of NFL success, which suggest that statistical discrimination and option value influence choices in this market.